Systematic literature review regarding hubris as a leadership phenomenon - Mármarosi, András; Németh, Gergely (Vezetéstudomány / Budapest Management Review, 2024)
As organisational development experts and academic scholars, the authors are increasingly frequently encountering the phenomenon of hubristic leadership. In relation to this topic, they were interested in the following questions: how does hubris evolve and how does a leader become hubristic? How does a leader’s environment react to these changes? What could be the potential benefits and risks for an organisation of having a hubristic leader? How does the relationship with the top management team appear? Finally, how could hubris be prevented or at least reined. To look for answers, the authors executed a systematic literature review. Based on a content analysis of the articles identified, they defined a problem map using a metasummary. Consequently, they determined four major themes. Based on detailed analysis of these four themes, the authors determined answers to most of their original questions and identified directions for future research.